Dyeing Parameters, Fastness and Ultraviolet Protection Properties of Nylon Dyed with Mangrove Bark Extract. (2019) - Vuthiganond, Nattaya; Nakpathom, Monthon; Somboon, Buppha; Narumol, Nootsara; Rungruangkitkrai, Nattadon; Mongkholrattanasit, Rattanaphol
Abstract: Investigation of dyeing parameters (temperature, time and pH), color fastness assessments and ultraviolet protection factor (UPF) of mangrove bark extract on nylon fabric were conducted. The optimum dyeing conditions were obtained at 90°C, 60 min and pH 5, respectively. Dyeing with different metal mordants (aluminium potassium sulfate, ferrous sulfate, copper sulfate, and stannous chloride) was also investigated. The ratings of color fastness testing showed that most of color fastness properties of dyed fabrics were generally acceptable except color fastness to washing due to considerable change in color of samples after subjected to washing test. Dyed nylon fabrics showed the improvement in UV-protection property.